Comparison between Effectiveness of Pomegranate Juice (Punica granatum) and Simvastatin for Lowering Blood LDL Level in Hypercholesterolemic Male Rats (Rattus novergicus) - Ariani, Ariani; Hawa, Putrya; Akhmad, Syaefudin Ali (Bangladesh Journal of Medical Science, 2016)
Background: Coronary heart disease (CHD) is one of the leading causes of death in developed and developing countries. In Indonesia 26% of death is caused by CHD. Hypercholesterolemia is one of the risk factors for CHD. Simvastatin is a hypolipidemic drug which has a significant number of side effects such as myopathy. While, Pomegranate juice (Punica granatum) contains anthocyanin, cathechins, tanin, vitamin C and vitamine E which have beneficial effects to decrease blood LDL level. Objective: The aim of this study was to compare the effectiveness of pomegranate juice (Punica granatum) and simvastatin in lowering blood LDL level of hypercholesterolemic male rats (Rattus novergicus). Methodology: This experimental study was executed following by pre and post control group design. This study used 15 male Wistar rats that were divided into three groups as 2% DMSO, simvastatin and pomegranate juice. Blood LDL level was examined at day-0 and day-15 of trial period. Result: Dependent T-test reveals that both pomegranate juice and simvastatin group showed significant difference in lowering blood LDL level before and after treatment. The result of Kruskal Wallis test showed that both pomegranate juice and simvastatin group have more significant efficacy than 2% DMSO. On the other hand, there was no significant difference between effectiveness of pomegranate juice and simvastatin group. Conclusion: Both Pomegranate juice and simvastatin are effective in lowering blood LDL level of hypercholesterolemia male rats and there is no significant difference between effectiveness of pomegranate juice and simvastatin. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.216-219